PENGEMBANGAN MEDIA PEMBELAJARAN DASAR LISTRIK DAN ELEKTRONIKA BERBASIS LECTORA INSPIRE DI SMK TARUNA PEKANBARU - Karnoto; Noverta Effendi; Witri Ramadhani (Unit Pelaksana Praktik Kependidikan Terpadu Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Riau, 2023)
At SMK Taruna Pekanbaru in the Basic Electronics subject, there are several obstacles experienced in learning such as a lack of interest and enthusiasm for student learning, the learning method used still uses the lecture method, and the learning media still fixated on using PowerPoint. The lack of use of varied and interesting learning media makes students feel bored and difficult to understand the basic lessons of electricity and electronics. Based on these problems, this development research aims to produce interactive learning media with Lectora Inspire on basic electricity and electronics material and to describe the feasibility of learning media with Lectora Inspire on basic electricity and electronics materials for class X TAV SMK Taruna Pekanbaru. The method used in this research is research and development (R&D). The development model used in the development of this interactive learning media is ADDIE. This research produces a product in the form of basic electrical electronics learning media for class X TAV students at SMK Taruna Pekanbaru. This basic electronics learning media was developed using the Lectora Inspire application. Learning media for basic electricity and electronics in terms of material aspects and benefits are categorized as good from the validation of material experts to be used as learning media for basic electricity and electronics. Based on the validation of media experts in terms of two aspects, namely the display aspect and the programming aspect, it is categorized as very good for use as a basic learning medium for electricity and electronics. As well as the teacher's assessment of three aspects, namely content quality and learning objectives, technical quality, and instructional quality which are categorized as good.